2022
DOI: 10.1002/cptc.202200154
|View full text |Cite
|
Sign up to set email alerts
|

Benzothiadiazole‐Based Green Hybridized Local and Charge‐Transfer (HLCT) Fluorophores as Solution‐Processed Non‐Doped Emitters for Simple Structured Electroluminescent Devices

Abstract: Herein, two new solution-processable HLCT fluorophores (CBzF and CBzFC) based on benzothiadiazole (Bz) derivatives were designed and synthesized (HLCT = hybridized local and charge transfer). Their optical and photophysical properties were experimentally and theoretically studied and verified by the solvatochromic effect and density functional theory calculations. The two molecules demonstrate high solubility, HLCT features, and an intense green fluorescence with solid-state photoluminescence quantum yields of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 97 publications
1
7
0
Order By: Relevance
“…However, the solvatochromic effect in the PL spectra is clearly observed with a change in the solvent polarity from low‐polarity triethylamine (TEA) to high‐polarity dimethylformamide (DMF). The PL spectra of the two compounds changed to a great extent from a narrow emission band peaked at 557 nm for TTBZ and 649 nm for TTNz (in TEA) to a broad emission band peaked at 688 nm for TTBz and 729 nm for TTNz (in DMF), that is, 80–131 nm red shift with a change in the solvent polarity is noteworthy and signifies the existence of CT components in their excited states as noted in other reports [14,29] . To better understand their solvatochromic effect, the linear fitting analysis of the Stokes shift (ν a ‐ν f ) vs solvent orientational polarizability ( f ) plotted according to the Lippert–Mataga (LM) model was evaluated [44] .…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…However, the solvatochromic effect in the PL spectra is clearly observed with a change in the solvent polarity from low‐polarity triethylamine (TEA) to high‐polarity dimethylformamide (DMF). The PL spectra of the two compounds changed to a great extent from a narrow emission band peaked at 557 nm for TTBZ and 649 nm for TTNz (in TEA) to a broad emission band peaked at 688 nm for TTBz and 729 nm for TTNz (in DMF), that is, 80–131 nm red shift with a change in the solvent polarity is noteworthy and signifies the existence of CT components in their excited states as noted in other reports [14,29] . To better understand their solvatochromic effect, the linear fitting analysis of the Stokes shift (ν a ‐ν f ) vs solvent orientational polarizability ( f ) plotted according to the Lippert–Mataga (LM) model was evaluated [44] .…”
Section: Resultssupporting
confidence: 76%
“…The μ e of the smaller slope is slightly greater than that of common LE fluorophores but close to that of a typical HLCT molecule N,N-diphenyl-4-(9phenylnaphthothiadiazol-4-yl)aniline (TPA-NZP) (μ e = 17.50 D), [13] while the μ e of the larger slope is close to that of a typical CT molecule 4-(N,N-dimethylamino)benzonitrile (DMABN) (μ e = 23 D). [45] In fact, some HLCT molecules exhibited LM plots with only one medium slope (μ e = 10.00-17.50 D), [14,26,46,47] this situation suggested that the CT and LE states might hybridize sufficiently, and such HLCT materials exhibited quasi-equivalent hybridization of CT and LE components. Hence, both TTBz and TTNz in high-polarity solvents (f � 0.15) retain a strong CT-emitting character, while in low-polarity solvents (f � 0.15), they behave like LE-emitting species with a small CT component or HLCT state emission formed in this solvent polarity region which was also illustrated through the solvatochromic experiments as mentioned above (Figure 2a).…”
Section: Chemphotochemmentioning
confidence: 97%
See 3 more Smart Citations